سعد الله ونّوس والاتجاه نحو المسرح التّسجيليّ دراسة تطبيقية في ( حفلة سمر من أجل/ 5/ حزيران ) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2013)
كانت نكسة حزيران /1967/ سبباً ليخلع ونّوس مظاهر مسرح لم يعد منسجماً مع واقعه، متنقّلاً من مرحلة العبث والوجوديّة إلى مرحلة أخرى اعتمدت التدخّل بالحدث السياسيّ والاجتماعيّ على نحو مباشر، وليُجسّد آلام الإنسان ضمن ظروفه التاريخيّة من خلال استخدام صيغة فنّية مسرحيّة جديدة، يهدف من ورائها إلى تغيير الواقع بعد تفسيره، وما دام اختار أن يكون شاهداً ومحاكماً ومديناً، فالشكل المسرحيّ التسجيليّ هو الأقرب إلى طبيعة الحدث المعالج؛ لأنّه من أشكال المسرح الواقعيّ، ومهمّته تسجيل المسرح بعد التعديلات اللاّزمة في الشّكل دون تغيير في المحتوى؛ لهذا اهتمّ بالإنسان، وارتبط بقضاياه، وسجّل الحدث التّاريخيّ، والدّوافع التي تحرّك الواقعة والفئات المشتركة فيها، وتزيل الأقنعة عن وجوه الرّموز الّتي تساعد على تثبيت الظلم وتمويه الحقائق. The setback of June /1967/ was a good reason for Wannous to change the theater forms which became inconsistent with his reality, Moving from absurd and existential stage to another stage adopted political and social intervention directly, representing human pain within historical circumstances by using a new artistry theatric formula, to change life after explaining it, and as long as he chooses to be a witness, a judge, and a libel, the theatrical documentary form was the closest to the intended nature of the event, because it is one of the theater realistic forms, and  its job is recording theater after the necessary adjustments in shape without the change in content; for that reason he focused his attention on human, linked to his issues, recorded the historic event and the motivations of the common categories of the incident, removing the masks from the faces of icons that increase injustice and distortion of facts.